An Analysis of Scholarly Studies Pertaining to the Lexicon Associated with Illnesses and Unhealthy States (Eurasian Medical Research Periodical, 2023)
Our article will delve into the theoretical aspects that pertain to defining the characteristics of the Dialectal Dictionary of Diseases. After careful consideration of the appropriate individuals to study the medical dictionary of diseases and conditions, we will divulge the distinctive linguistic characteristics of this section and the techniques used in its creation. The science community thoroughly examines the classifications of this glossary which includes detailed explanations of the distinct names and cases of diseases in different dialects. Observations have been made regarding the distinctions between folk medical language and scientific language.